EXPRESSIVE SPEECH ACTS IN BLACKPINK INTERVIEWS ON AMERICAN TALK SHOWS - Eunike Kyudasai Louis Bramajaya; Yuli Widiana (Humaniora Scientia, 2023)
Comprehending the speech acts theory is crucial in communication. The aim of this research is to identify the types and to describe the function of expressive speech act in Blackpink interviews on American talk shows. This research is classified as qualitative descriptive research. The data of this research were words, phrases, and clauses that contain expressive speech acts found in the videos of Blackpink and the hosts in American talk shows that were published from 2019 to 2022. The technique of collecting data was conducted by transcribing the English subtitle of Blackpink interviews on American talk shows, classifying the type of expressive speech acts, and the last is coding the data. The result revealed that there were five types of expressive speech acts used by the hosts and Blackpink, such as apologizing, congratulating, praising, attitude, and thanking. Apologizing functions as a form of self-acceptance for a mistake that has been made. Furthermore, congratulating functions as a form of appreciation for someone's achievement while praising functions to make the person being praised feel comfortable and happy. Attitude functions to make the interlocutor understand what the speakers feel. Thanking functions to show gratitude and respond to statements made by the speaker. In general, expressive speech acts are used on the talk show to involve viewersâ€™ emotions as a part of entertainment.Â Keywords: Pragmatics, Expressive Speech Acts, Talk Show, Expressive function